Error Patterns in Senior High School Students’ Descriptive Texts Through Surface Strategy Taxonomy - Alfa Rizky Cahya Bagaskara; Abdul Ngafif; Basuki (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study investigates error patterns in senior high school students’ descriptive texts using the Surface Strategy Taxonomy framework, which classifies errors into omission, addition, misordering, and misinformation. While previous studies have examined writing errors on Surface Strategy Taxonomy error categories on descriptive texts at the secondary level, few analyze deeper into more detailed categories of writing errors occured. This leaves a gap in understanding how students struggle with grammatical accuracy in this genre. The current research aimed to identify the most frequent types of errors and analyze the kind of mistakes that occurred in each. A descriptive qualitative design was employed, with 36 descriptive texts of students at SMA Negeri 7 Purworejo during the 2025/2026 academic year. The texts were analyzed to classify and calculate the frequency of each error type. The findings revealed that students produced all four categories of errors, with misinformation accounting for the highest proportion (45%), followed by omission (39%), addition (14%), and misordering (2%). These results indicate that learners often struggle with selecting appropriate grammatical forms, functional words, and word order, reflecting both interlanguage development and first language transfer. This study analyzes student errors while contributing to pedagogical practice by offering diagnostic insights into writing errors and identifying areas requiring explicit instruction and corrective feedback. The findings provide diagnostic insights for EFL teachers to design targeted instruction and improve students’ grammatical accuracy in writing.